Preparation method of interlayer cross-linked polyimide three-layer composite film
By introducing copper chloride and side chain carboxydiamine monomers into the polyimide film, the interlayer crosslinking structure is formed, which solves the problems of unstable dielectric constant and large dielectric loss at high temperatures, and improves the film The dielectric constant and breakdown strength achieve the stability and energy storage density of high-temperature energy storage films.
Patent Information
- Application Number
- CN202411421734.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-31
AI Technical Summary
The problems of existing thin film capacitors with unstable dielectric constant, large dielectric loss and low breakdown strength in high temperature environments limit their use and energy storage density in harsh high temperature environments.
The preparation method of polyimide three-layer composite film with interlayer crosslinking is adopted. By introducing copper chloride and side chain carboxydiamine monomers into the polyimide film, the copper ions are used to form a coordination cross with imidazole groups. to enhance interface interaction force, and to improve dielectric constant and breakdown strength through dynamic hydrogen bonding and coordination crosslinking.
It effectively improves the dielectric constant and breakdown strength of the polyimide film, reduces dielectric loss, enhances the interface interaction force, extends the breakdown path, and improves the energy storage density and high temperature stability of the film.
Smart Images

Figure CN119217618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of a polyimide film and its preparation and its application in film capacitors, and in particular to a method for preparing an interlayer cross-linked polyimide three-layer composite film. Background Art
[0002] As a physical energy storage device, electrostatic capacitors have the advantages of high-frequency rapid charging and discharging, high discharge efficiency, low loss, and large capacity. They are widely used in aerospace launches, medical pulse discharges, hybrid vehicles, audio equipment, etc. However, electrostatic capacitors still have the disadvantages of low energy density and low operating temperature. They usually need to be equipped with water cooling devices to ensure their normal operation. Compared with ceramic capacitors, film capacitors have the advantages of low loss, high breakdown strength, and flexible winding. The discharge energy density and discharge efficiency of the film can be improved by improving the dielectric constant and breakdown strength of the film and reducing the dielectric loss. Usually, while increasing the dielectric constant of the material, it will lead to an increase in dielectric loss and a decrease in breakdown strength. This mutually restrictive relationship makes it difficult to significantly increase the discharge energy density of film capacitors.
[0003] The most widely used film capacitor material is biaxially oriented polypropylene, which has ultra-low dielectric loss (loss angle <0.0002) and high breakdown strength. However, the low dielectric constant (~2.2) makes the biaxially oriented polypropylene material have a low discharge energy density (1~2 J / cm 3 ), and its operating temperature (<70 ℃) also limits its use in high temperature and harsh environments. Therefore, the development of materials with both high energy storage density and high temperature resistance is of great significance to the future development of film capacitors.
[0004] Polyimide materials have the advantages of high temperature resistance, excellent mechanical properties, good electrical insulation properties, good high-frequency performance, and low dielectric loss. They are suitable for high-temperature resistant thin film capacitor materials. However, there are still problems such as low breakdown strength, unstable dielectric properties at high temperatures, and increased dielectric loss. High dielectric ceramic nanomaterials, conductive carbon nanotubes, metal ions, etc. can be introduced into the film to improve its dielectric constant; large volume groups such as trifluoromethyl, cross-linking, multi-layer composites, etc. can also be introduced to reduce dielectric loss and improve breakdown strength. Summary of the invention
[0005] The main technical problem solved by the present invention is to provide a method for preparing a three-layer composite film of polyimide with interlayer cross-linking. A three-layer composite film is prepared, in which cupric chloride is introduced to more effectively improve the problem of poor interlayer interface compatibility, while improving the dielectric constant and breakdown strength of the polyimide film, which is of great significance for improving the energy storage density of the film. The cross-linking effect can reduce the molecular chain movement at 150°C, thereby alleviating the problems of unstable dielectric constant and large dielectric loss at high temperature, and providing a solution for the production of high-temperature energy storage films.
[0006] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a method for preparing a three-layer composite film of polyimide with interlayer crosslinking, comprising the following steps: S1. Prepare solution A, solution B and solution C; S2, adjusting the insertion height of the scraper to 30 μm, scraping solution A onto a glass plate, and removing the solvent after vacuum degassing and drying at 60 °C for 1 h to obtain a bottom PAA film; S3, adjusting the insertion height of the scraper to 20 μm, scraping solution C on the 1st layer, drying it at 60 °C in vacuum for 0.5 h, removing the solvent and setting it aside; S4, adjusting the insertion height of the scraper to 30 μm, scraping solution B on the glass plate, vacuum degassing, and drying at 60 °C for 1 h to remove the solvent to obtain the intermediate layer PAA film; S5. Repeat steps S3 and S2 to obtain a top PAA film, subject the bottom PAA film, the middle PAA film and the top PAA film to vacuum thermal imidization, and finally demold to obtain a polyimide three-layer composite film with self-supporting properties.
[0007] In a preferred embodiment of the present invention, the preparation of solution A comprises the following steps: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, and then the diamine monomer DADC was added and stirred thoroughly to completely dissolve it. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask and stirred thoroughly. Then, the dianhydride monomer 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride was added in a 1.05-fold molar ratio with the two diamines in three times. The solid content of the solution was 13%, and stirring was continued at a low temperature of 5°C for 48 h to obtain solution A.
[0008] In a preferred embodiment of the present invention, the molar ratio of the diamine monomer DADC to 2-(diaminophenyl)benzimidazole-5-amine is 10:90.
[0009] In a preferred embodiment of the present invention, the preparation of the diamine monomer DADC comprises the following steps: First, 60 mL of THF after dehydration by a quaternary molecular sieve was poured into a three-necked flask with protective gas N2, and cooled in an ice-water bath, and 0.04 mol of 5-aminoisophthalic acid was added. After stirring evenly, 3,5-dinitrobenzoyl chloride in an equal molar ratio was added in batches to react to generate a first white product. Thin layer chromatography TLC spot plate was used to determine whether the monomer was completely reacted. During this period, a slightly excessive amount of 3,5-dinitrobenzoyl chloride was added in an appropriate amount. After the reaction was completed, the first white product was filtered to obtain a first crude product, which was then washed in ethyl acetate, filtered out again, and finally dried in a vacuum oven at 80°C for 12 h to obtain a nitro product DNBC. Under nitrogen protection, 100 mL of anhydrous ethanol was added to the three-necked flask, and then 5 g of DNBC was weighed and added to the three-necked flask, and then 5 wt% of Pd / C was added. After the temperature was raised to 80 °C and refluxed, 20 mL of hydrazine hydrate was slowly added dropwise. The reaction endpoint was determined by TLC spot plate. After the reaction was completed, the product was completely dissolved, and the catalyst Pd / C was filtered out. Then the filtrate was poured into a three-necked flask, cooled with an ice water bath, and then HCl was slowly added dropwise to adjust the pH value to 1 ~ 2. It was allowed to stand in a refrigerator for 12 h until it was completely precipitated to obtain a second crude product. The second crude product was filtered to obtain a white powder, which was then redissolved in deionized water, and then HCl was added to precipitate and filtered. This process was repeated two to three times to remove impurities. Finally, the amino hydrochloride product was obtained, placed in a vacuum oven at 60 °C for drying, the product was placed in ethanol and neutralized with triethylamine, the pH value was adjusted to 7 ~ 8 to free the amino group, and then washed with ethanol, and the product was filtered and placed in a vacuum oven for low temperature drying for 24 h, to obtain a white final product.
[0010] In a preferred embodiment of the present invention, the yield of the nitro product DNBC is 75% to 80%.
[0011] In a preferred embodiment of the present invention, the diamine monomer DADC is prepared under light-protection conditions throughout the entire process.
[0012] In a preferred embodiment of the present invention, the preparation of solution B comprises the following steps: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, followed by the addition of diamine monomer 3,5-diaminobenzoic acid, which was stirred thoroughly to dissolve completely. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask, stirred thoroughly, and then the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride was added in three times with a 1.05-fold molar ratio of the two diamines. The solid content of the solution was 13%, and stirring was continued at a low temperature of 5°C for 48 h to obtain solution B.
[0013] In a preferred embodiment of the present invention, the molar ratio of the diamine monomer 3,5-diaminobenzoic acid to 2-(diaminophenyl)benzimidazole-5-amine is 10:90.
[0014] In a preferred embodiment of the present invention, the preparation of solution C comprises the following steps: Cupric chloride is dissolved in dimethylacetamide to prepare a cupric chloride solution with a solid content of 0.2% to 0.3% to obtain solution C.
[0015] In a preferred embodiment of the present invention, a gradient temperature rise method is used to thermally imidize the polyimide three-layer composite film, and the temperature and time used are as follows: (1) 1 h at 100 °C; (2) 1 h at 200 °C; (3) 1 h at 300 °C; (4) 0.5h at 350℃.
[0016] The beneficial effects of the present invention are as follows: the interlayer cross-linked polyimide three-layer composite film obtained by the present invention contains carboxyl structures in the upper and lower surfaces and the middle layer, which can generate dynamic hydrogen bonds, thereby increasing the interaction between interfaces; copper chloride is introduced between the layers and dissolved in an organic solvent to prepare a solution C, and the copper ions and imidazole groups are used to form coordination cross-linking to prepare a three-layer composite film with interlayer cross-linking effect, thereby further strengthening the interface interaction force; the synthesized side chain carboxyl-containing diamine monomer can increase the molecular chain spacing and reduce the dielectric loss, and the high polarization strength of the carboxyl group can simultaneously increase the dielectric constant; the introduction of copper chloride can increase the ion polarization strength and thus improve the dielectric constant, and the existence of the coordination cross-linking effect inhibits the movement of free charges and reduces the increase in loss; the interlayer cross-linked three-layer composite film has strong interaction between interfaces, and there are two forms of coordination cross-linking and hydrogen bond cross-linking, which can effectively extend the breakdown path and increase the breakdown strength, and finally achieve the simultaneous increase of the dielectric constant and the breakdown strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which: Figure 1 It is a schematic diagram of the preparation process and interlayer cross-linking structure of the present invention; Figure 2 It is a schematic diagram of the synthesis route of DADC in the present invention; Figure 3The present invention provides a thin film structure design and synthesis route of solution A and solution B; Figure 4 It is a schematic diagram of the optimized three-dimensional molecular structure and interlayer interaction force of the present invention; Figure 5 Schematic diagram of dielectric constant and loss factor of the polyimide three-layer composite film of the present invention at high frequency; Figure 6 It is a schematic diagram of the breakdown strength of the polyimide three-layer composite film of the present invention. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] See also Figure 1-6 , the embodiments of the present invention are: Example 1
[0020] A method for preparing a three-layer cross-linked polyimide composite film comprises the following steps: S1. Prepare solution A, solution B and solution C; S2, adjusting the insertion height of the scraper to 30 μm, scraping solution A onto a glass plate, and removing the solvent after vacuum degassing and drying at 60 °C for 1 h to obtain a bottom PAA film; S3, adjusting the insertion height of the scraper to 20 μm, scraping solution C on the 1st layer, drying it at 60 °C in vacuum for 0.5 h, removing the solvent and setting it aside; S4, adjusting the insertion height of the scraper to 30 μm, scraping solution B on the glass plate, vacuum degassing, and drying at 60 °C for 1 h to remove the solvent to obtain the intermediate layer PAA film; S5, after repeating step S3 and step S2 to obtain a top PAA film, the bottom PAA film, the middle PAA film and the top PAA film are subjected to vacuum thermal imidization, and the polyimide three-layer composite film is thermally imidized by a gradient temperature rise method, and the temperature and time used are as follows: (1) 1 h at 100 °C; (2) 1 h at 200 °C; (3) 1 h at 300 °C; (4) 0.5h at 350℃ Finally, the three-layer polyimide composite film with self-supporting performance was obtained by demoulding. The dielectric constant and breakdown strength of the obtained self-supporting film were improved. The data are as follows Figure 5 Figure 6 shown.
[0021] The film containing BTDA-BIA-DADC structure was selected as the middle layer because the dielectric constant of this structure is relatively high, while the upper and lower surface layers selected structures with relatively low dielectric constant and relatively strong rigidity, which is beneficial to ensure its stability under high voltage and improve the breakdown strength. The purity of the drugs used and the manufacturers are shown in Table 1.
[0022] Table 1 Purity and manufacturer of the drugs used Example 2
[0023] The preparation of solution A includes the following steps: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, and then the diamine monomer DADC was added and stirred thoroughly to make it completely dissolved. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask and stirred thoroughly. The molar ratio of the diamine monomer DADC to 2-(diaminophenyl)benzimidazole-5-amine was 10:90. Then, the dianhydride monomer 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride was added three times with a molar ratio of 1.05 times that of the two diamines. The solid content of the solution was 13%. The solution was stirred continuously at a low temperature of 5°C for 48 h to obtain solution A, and the PAA film was prepared by the cast film method. The synthesis process is as follows: Figure 3 Solution A shown, The selected diamine monomer DADC has a side chain dicarboxyl group that can increase the molecular chain spacing and reduce loss. Figure 3 It can be seen that after the introduction of DADC monomer, the molecular chain is more twisted and the molecular distance is increased; in addition, the two carboxyl groups contained in it also effectively increase the polarization strength, thereby achieving the improvement of dielectric constant while reducing dielectric loss; the carbonyl structure contained in the anhydride monomer selected by the diamine monomer increases the conjugation effect, which is beneficial to electron transmission and improves the dielectric constant.
[0024] Wherein, the preparation of the diamine monomer DADC comprises the following steps: First, 60 mL of THF after dehydration through a quaternary molecular sieve was poured into a three-necked flask with protective gas N2, and cooled in an ice-water bath, 0.04 mol of 5-aminoisophthalic acid was added, and after stirring evenly, 3,5-dinitrobenzoyl chloride in an equal molar ratio was added in batches to react to generate a first white product. Thin layer chromatography TLC spot plate was used to determine whether the monomer was completely reacted. During this period, a slightly excessive amount of 3,5-dinitrobenzoyl chloride was added in an appropriate amount. After the reaction was completed, the first white product was filtered to obtain a first crude product, which was then placed in ethyl acetate for washing, filtered out again, and finally placed in a vacuum oven for drying at 80°C for 12 h to obtain the nitro product DNBC. The yield of the nitro product DNBC was about 80%.
[0025] Under nitrogen protection, 100 mL of anhydrous ethanol was added to the three-necked flask, and then 5 g of DNBC was weighed and added to the three-necked flask, and then 5 wt% of Pd / C was added. After the temperature was raised to 80 °C and refluxed, 20 mL of hydrazine hydrate was slowly added dropwise. The reaction endpoint was determined by TLC spot plate. After the reaction was completed, the product was completely dissolved, and the catalyst Pd / C was filtered out. Then the filtrate was poured into a three-necked flask, cooled with an ice water bath, and then HCl was slowly added dropwise to adjust the pH value to 1 ~ 2. It was allowed to stand in a refrigerator for 12 h until it was completely precipitated to obtain a second crude product. The second crude product was filtered to obtain a white powder, which was then redissolved in deionized water, and then HCl was added to precipitate and filtered. This process was repeated two to three times to remove impurities. Finally, the amino hydrochloride product was obtained, placed in a vacuum oven at 60 °C for drying, the product was placed in ethanol and neutralized with triethylamine, the pH value was adjusted to 7 ~ 8 to free the amino group, and then washed with ethanol, and the product was filtered and placed in a vacuum oven for low temperature drying for 24 h, a white final product was obtained. The diamine monomer DADC was prepared under light-protection conditions throughout the entire process, and the yield was about 73%. Example 3
[0026] Preparation of Solution B The preparation method of Solution A is similar, except that the diamine monomer DCDA and the dianhydride monomer BTDA are replaced by the diamine monomer 3,5-diaminobenzoic acid (DABA) and the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) in the same proportions. The synthesis process is as follows: Figure 3 Solution B shown.
[0027] The steps include: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, and then the diamine monomer 3,5-diaminobenzoic acid was added and stirred thoroughly to completely dissolve it. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask and stirred thoroughly. The molar ratio of the diamine monomer 3,5-diaminobenzoic acid to 2-(diaminophenyl)benzimidazole-5-amine was 10:90. Then, the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride was added in three times with a molar ratio of 1.05 times the two diamines. The solid content of the solution was 13%. Stirring was continued at a low temperature of 5°C for 48 h to obtain solution B.
[0028] The biphenyl structure contained in the selected anhydride BPDA and the benzimidazole structure in BIA are rigid, which can increase the heat resistance of the film and improve its dielectric stability at high temperatures; in addition, the imidazole group in BIA can form a coordination cross-linking effect with copper ions to increase the interlayer interaction force; the carboxyl group in the selected DABA can form a hydrogen bond with the carboxyl group in DADC, making the interfacial interaction force stronger. The schematic diagram of the hydrogen bond and coordination bond is shown in Figure 4 shown. Example 4
[0029] The preparation of solution C includes the following steps: Cupric chloride was dissolved in dimethylacetamide to prepare a cupric chloride solution with a solid content of 0.2% to 0.3%, and solution C was obtained. The three-layer film was prepared by layer-by-layer coating, such as Figure 1 shown.
[0030] In summary, the product obtained by the preparation method of a three-layer composite film of polyimide with interlayer crosslinking pointed out by the present invention has the following beneficial effects: the upper and lower surfaces and the middle layer both contain carboxyl structures that can produce dynamic hydrogen bonds, thereby increasing the interaction between interfaces; copper chloride is introduced between the layers and dissolved in an organic solvent to prepare a solution C, and copper ions and imidazole groups are used to form coordination crosslinks to prepare a three-layer composite film with interlayer crosslinking, thereby further strengthening the interface interaction force; the synthesized side chain carboxyl-containing diamine monomer can increase the molecular chain spacing and reduce dielectric loss, and the high polarization strength of the carboxyl group can simultaneously increase the dielectric constant; the introduction of copper chloride can increase the ion polarization strength and thus increase the dielectric constant, and the presence of coordination crosslinking inhibits the movement of free charges and reduces the increase in loss; the three-layer composite film with interlayer crosslinking has strong interaction between interfaces, and there are two forms of coordination crosslinking and hydrogen bond crosslinking, which can effectively extend the breakdown path and increase the breakdown strength, and finally achieve the simultaneous increase of the dielectric constant and the breakdown strength.
[0031] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a three-layer cross-linked polyimide composite film, characterized in that: The steps include: S1. Prepare solution A, solution B and solution C; S2, adjusting the insertion height of the scraper to 30 μm, scraping solution A onto a glass plate, and removing the solvent after vacuum degassing and drying at 60 °C for 1 h to obtain a bottom PAA film; S3, adjusting the insertion height of the scraper to 20 μm, scraping solution C on the 1st layer, drying it at 60 °C in vacuum for 0.5 h, removing the solvent and setting it aside; S4, adjusting the insertion height of the scraper to 30 μm, scraping solution B on the glass plate, vacuum degassing, and drying at 60 °C for 1 h to remove the solvent to obtain the intermediate layer PAA film; S5. Repeat steps S3 and S2 to obtain a top PAA film, subject the bottom PAA film, the middle PAA film and the top PAA film to vacuum thermal imidization, and finally demold to obtain a polyimide three-layer composite film with self-supporting properties.
2. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 1, characterized in that: The preparation of solution A includes the following steps: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, and then the diamine monomer DADC was added and stirred thoroughly to completely dissolve it. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask and stirred thoroughly. Then, the dianhydride monomer 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride was added in a 1.05-fold molar ratio with the two diamines in three times. The solid content of the solution was 13%, and stirring was continued at a low temperature of 5°C for 48 h to obtain solution A.
3. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 2, characterized in that: The molar ratio of the diamine monomer DADC to 2-(diaminophenyl)benzimidazole-5-amine is 10:
90.
4. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 2, characterized in that: The preparation of the diamine monomer DADC comprises the following steps: First, 60 mL of THF after dehydration by a quaternary molecular sieve was poured into a three-necked flask with protective gas N2, and cooled in an ice-water bath, and 0.04 mol of 5-aminoisophthalic acid was added. After stirring evenly, 3,5-dinitrobenzoyl chloride in an equal molar ratio was added in batches to react to generate a first white product. Thin layer chromatography TLC spot plate was used to determine whether the monomer was completely reacted. During the reaction, a slightly excessive amount of 3,5-dinitrobenzoyl chloride was added in an appropriate amount. After the reaction was completed, the first white product was filtered to obtain a first crude product, which was then washed in ethyl acetate, filtered out again, and finally dried in a vacuum oven at 80 ° C for 12 h to obtain a nitro product DNBC; Under nitrogen protection, 100 mL of anhydrous ethanol was added to the three-necked flask, and then 5 g of DNBC was weighed and added to the three-necked flask, and then 5 wt% of Pd / C was added. After the temperature was raised to 80 °C and refluxed, 20 mL of hydrazine hydrate was slowly added dropwise. The reaction endpoint was determined by TLC spot plate. After the reaction was completed, the product was completely dissolved, and the catalyst Pd / C was filtered out. Then the filtrate was poured into a three-necked flask, cooled with an ice water bath, and then HCl was slowly added dropwise to adjust the pH value to 1 ~ 2. It was allowed to stand in a refrigerator for 12 h until it was completely precipitated to obtain a second crude product. The second crude product was filtered to obtain a white powder, which was then redissolved in deionized water, and then HCl was added to precipitate and filtered. This process was repeated two to three times to remove impurities. Finally, the amino hydrochloride product was obtained, placed in a vacuum oven at 60 °C for drying, the product was placed in ethanol and neutralized with triethylamine, the pH value was adjusted to 7 ~ 8 to free the amino group, and then washed with ethanol, and the product was filtered and placed in a vacuum oven for low temperature drying for 24 h, to obtain a white final product.
5. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 4, characterized in that: The yield of the nitro product DNBC is 75% to 80%.
6. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 4, characterized in that: The diamine monomer DADC was prepared in a light-protected manner.
7. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 1, characterized in that: The preparation of solution B includes the following steps: Under N2 protection, N,N-dimethylacetamide was poured into a three-necked flask, followed by the addition of diamine monomer 3,5-diaminobenzoic acid, which was stirred thoroughly to dissolve completely. Then, 2-(diaminophenyl)benzimidazole-5-amine was added to the three-necked flask, stirred thoroughly, and then the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride was added in three times with a 1.05-fold molar ratio of the two diamines. The solid content of the solution was 13%, and stirring was continued at a low temperature of 5°C for 48 h to obtain solution B.
8. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 7, characterized in that: The molar ratio of the diamine monomer 3,5-diaminobenzoic acid to 2-(diaminophenyl)benzimidazole-5-amine is 10:
90.
9. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 1, characterized in that: The preparation of solution C includes the following steps: Cupric chloride is dissolved in dimethylacetamide to prepare a cupric chloride solution with a solid content of 0.2% to 0.3% to obtain solution C.
10. The method for preparing the interlayer cross-linked polyimide three-layer composite film according to claim 1, characterized in that: The thermal imidization of the polyimide three-layer composite film was carried out by the gradient temperature rising method, and the temperature and time used were as follows: (1) 1 h at 100 °C; (2) 1 h at 200 °C; (3) 1 h at 300 °C; (4) 0.5h at 350℃.